Analysis of Lateral Buckling of Bar with Axial Force Accumulation in Truss - Nuttapon Wattanamankong; Arthit Petchsasithon; Suwat Dhirasedh (My University, 2017)
This research studies the lateral buckling behavior in truss and lateral buckling coefficient of truss. Lateral buckling analysis of truss is performed by simulating the structural model with both end supports being pinned and roller-supports. The analysis is indirectly conducted using Elastic Theory to evaluate the length of lateral buckling by calculating the determinant of the Matrix [K]. Results from the analysis are marginally different from those obtained from finite element program and are considerably less than those obtained from Eurocode standard. This can be concluded that using elastic theory to evaluate lateral buckling coefficient of truss member will result in more economical section.
Keywords: Eurocode; Bar (unit); Structural Load-Bearing Analysis